Spexin Friend or Foe? Novel Role of Spexin During Thermogenesis of White Adipose Tissue - Gambaro, Sabrina E (J Endocr Soc, 2021)
Spexin (SPX) is a novel adipokine playing an emerging role in metabolic diseases due to its involvement in carbohydrate homeostasis, weight loss, appetite control, gastrointestinal movement, among others. Moreover, plasma levels are reduced in obese and type II diabetic patients. In vitro, SPX favors lipolysis in adipocytes and hepatocytes and inhibits white adipogenesis. Therefore, the aim of this study was to evaluate the role of SPX in white adipose tissue (AT) thermogenesis. C57BL/6J male mice were treated or not with SPX for ten days (ip. 29 µg/kg/day; CTR and SPX). At day 3 mice were randomly divided: a group was kept at room temperature (RT) and the other at 4°C to stimulate thermogenesis (CTR-C and SPX-C). Caloric intake and body weight was daily recorded. At the end of the protocol plasma, Brown AT (BAT), abdominal AT (Epidydimal, EAT) and subcutaneous AT (Inguinal, IAT) depots were collected for several measurements. We found that caloric intake was increased when animals were exposed to cold (P<0.001). Body weight change revealed a differential effect of SPX depending on temperature (interaction SPX x Cold, P<0.05): SPX animals weighted less than CTR at RT, but upon cold stimulation there was no difference. No changes were observed for plasma glucose levels, however plasma triglycerides (Tg) levels decreased after cold exposure regardless SPX treatment (Cold P<0.01). Liver Tg content showed a SPX x Cold interaction effect (P<0.0001), where, upon cold stimulation, CTR-C animals increased their levels, but on the contrary SPX-C mice decreased it. EAT, IAT and BAT relative mass showed an interaction effect of variables (SPX x Cold P<0.05). When compared upon cold, SPX-C mice had less AT mass compared to CTR-C mice. IAT and EAT mRNA expression of UCP1 and Cox8b showed SPX x Cold interaction (P<0.05), with a tendency of reduction or no difference in SPX at RT, but with a significant decrease in SPX-C compared to CTR-C mice upon cold exposure. PGC1a expression was increased in EAT from cold exposed-mice and in IAT only in CTR-C mice. UCP1 protein levels showed different results depending on the AT depot. For IAT SPX x Cold interaction (P<0.05) was observed, where SPX inhibited UCP1 stimulation only upon cold exposure. On the contrary, for EAT UCP1 levels decreased in SPX-treated mice, regardless cold exposure (SPX P<0.05). In conclusion, SPX treatment in vivo reduced the thermogenic process in subcutaneous and abdominal AT, being more evident upon cold stimulation. PICT2017-2038, PICT2017-2314.